Harbour porpoises in the Aegean Sea, Eastern Mediterranean: the species' presence is confirmed. Issue 1 (December 2016) - Cucknell, A-C; Frantzis, A.; Boisseau, O.; Romagosa, M.; Ryan, C.; Tonay, A.; Alexiadou, P.; Öztürk, A.; Moscrop, A.
Abstract Results are presented from the first systematic visual and acoustic line-transect survey for harbour porpoises in the Thracian Sea, northern Aegean Sea. During the vessel survey, undertaken in summer 2013, porpoises were observed on nine occasions and detected acoustically 16 times, with a total of 21 distinct encounters recorded. Harbour porpoises were encountered in three discrete blocks: north of the Island of Thasos, Greece; south and west of the city of Alexandroupolis, Greece; and in Saros Bay, Turkey. Saros Bay exhibited the highest relative acoustic encounter rate of harbour porpoises, and porpoises were observed visually there on two occasions 14 days apart, in small groups, one of which included a mother-calf pair. A comprehensive review of stranding records is also presented. The three areas identified as harbour porpoise habitat in this study coincide with the highest number of recorded stranded animals. This paper is the first to report free-swimming harbour porpoises in the Aegean Sea since 1993, and the first time ever in Turkish Aegean waters. Now that the presence of harbour porpoises has been documented, international cooperation towards long term monitoring and management measures are urgently required in order to conserve this vulnerable population.